Clostridium perfringens phospholipase C, an archetypal bacterial virulence factor, induces the formation of extracellular traps by human neutrophils - Badilla-Vargas, Lisa; Pereira, Reynaldo; Molina-Mora, José Arturo; Alape-Girón, Alberto; Flores-Díaz, Marietta (Frontiers in cellular and infection microbiology, 2023)
Neutrophil extracellular traps (NETs) are networks of DNA and various microbicidal proteins released to kill invading microorganisms and prevent their dissemination. However, a NETs excess is detrimental to the host and involved in the pathogenesis of various inflammatory and immunothrombotic diseases. Clostridium perfringens is a widely distributed pathogen associated with several animal and human diseases, that produces many exotoxins, including the phospholipase C (CpPLC), the main virulence factor in gas gangrene. During this disease, CpPLC generates the formation of neutrophil/platelet aggregates within the vasculature, favoring an anaerobic environment for C. perfringens growth. This work demonstrates that CpPLC induces NETosis in human neutrophils. Antibodies against CpPLC completely abrogate the NETosis-inducing activity of recombinant CpPLC and C. perfringens secretome. CpPLC induces suicidal NETosis through a mechanism that requires calcium release from inositol trisphosphate receptor (IP 3 ) sensitive stores, activation of protein kinase C (PKC), and the mitogen-activated protein kinase/extracellular signal-regulated kinase (MEK/ERK) pathways, as well as the production of reactive oxygen species (ROS) by the metabolism of arachidonic acid. Proteomic analysis of the C. perfringens secretome identified 40 proteins, including a DNAse and two 5´-nucleotidases homologous to virulence factors that could be relevant in evading NETs. We suggested that in gas gangrene this pathogen benefits from having access to the metabolic resources of the tissue injured by a dysregulated intravascular NETosis and then escapes and spreads to deeper tissues. Understanding the role of NETs in gas gangrene could help develop novel therapeutic strategies to reduce mortality, improve muscle regeneration, and prevent deleterious patient outcomes.